Management of Forest Fire: a Case study in Manesht and Ghalarang Protected Areas, of Ilam Province in Iran - Nazari, Rahim; Nasiri, Parvin; Gharagoozloo, Ali Reza; Mansoori, Nabiollah (International Journal of Bio-resource and Stress Management, 2023)
Forest firing seems to be an instant natural crisis, so crisis management program development and its implementation will be very effective in protecting these areas. Prevention is one of the most important stages of such measure in identifying the hazards and responsible factors as well. The applications of Geographic Information System (GIS) and Remote Sensing (RS) are very diverse in the management of forest fire crisis. Fire risk zone mapping, forest fire modeling, and effective management of the resources and the equipment in time of fire and in different stages of crisis management are among the most effective applications. In this study, fire risk zone map of Manesht and Ghalarang protected areas (30,000 ha), located in Ilam province, western forests of Iran, was prepared. At first, a model of land use layers, forest reservoirs, wildlife habitats, plant species and vegetative cover density, population density maps, distance from roads, farmlands and tourism favorable areas, slope, aspect and elevation, was prepared using the Analytical Hierarchy Process (AHP) and fire risk zone mapping was performed based on the definition of risk (which is the product of occurrence probability multiplied by consequence intensity). The area diagram of risk zone mapping classes is a normal bell-shaped curve. The area with mean and high or low risk classes were 78 and 10%, respectively. The statistics showed that 23 of 25 cases of the forest fire in 2010 occurred in areas with mean to very high risk classes.